Hubungan Antara Kepercayaan Diri Dengan Penyesuaian Diri Siswa Kelas VII UPTD SMP Negeri 11 Kota Kupang - Jawan, Kristina Beso; Erlinda, Maria; Lio, Stefanus (Penerbit Widina, Widina Media Utama, 2025)
The purpose of this study is to examine the relationship between self-confidence and self-adjustment among seventh-grade students in class VII-G at UPTD SMP Negeri 11 Kota Kupang in the 2024/2025 academic year. This study uses a quantitative approach. The independent variable (X) is self-confidence, while the dependent variable (Y) is self-adjustment. The population and sample consist of 32 seventh-grade students in the 2024/2025 academic year. Data were collected using questionnaires, and analysis was performed using Pearson's product-moment correlation. The analysis produced a correlation coefficient in the range of 0.60–0.799 and a significance value of 0.000 0.05. These findings indicate a significant relationship between self-confidence and self-adjustment among seventh-grade students at UPTD SMP Negeri 11 Kota Kupang in the 2024/2025 academic year.ABSTRAKTujuan penelitian ini adalah untuk mengkaji hubungan antara kepercayaan diri dan penyesuaian diri di kalangan siswa kelas VII-G di UPTD SMP Negeri 11 Kota Kupang pada tahun ajaran 2024/2025. Penelitian ini menggunakan pendekatan kuantitatif. Variabel independen (X) adalah kepercayaan diri, sedangkan variabel dependen (Y) adalah penyesuaian diri. Populasi dan sampel terdiri dari 32 siswa kelas VII-G pada tahun ajaran 2024/2025. Data dikumpulkan menggunakan kuesioner, dan analisis dilakukan melalui korelasi momen produk Pearson. Analisis menghasilkan koefisien korelasi dalam rentang 0,60–0,799 dan nilai signifikansi 0,000 0,05. Temuan ini menunjukkan adanya hubungan yang signifikan antara kepercayaan diri dan penyesuaian diri di kalangan siswa kelas VII di UPTD SMP Negeri 11 Kota Kupang pada tahun ajaran 2024/2025.